Elderly and Prostate Cancer Screening - Stamatiou, Konstantinos N (Urology Journal, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Purpose: To discuss the issue of screening for prostate cancer in elderly individuals. The impact of life expectancy on the choice of treatment in both patients and health care providers has been investigated as well. Materials and Methods: We identified studies published from 1990 onwards by searching the MEDLINE database of the National Library of Medicine. Initial search terms were “localized prostate cancer” and “early stage prostate cancer” combined with “elderly patients, life expectancy, palliative, curative, quality of life, watchful waiting, radical prostatectomy, brachytherapy, and external beam radiotherapy”. Results: Despite the decrease in prostate carcinoma-specific mortality, the use of prostate-specific antigen (PSA) has been shown to increase the prostate cancer detection rate with a shift to detection at earlier and less invasive pathological stages, overriding concerns about over-diagnosis and over treating. However, PSA screening is mainly offered to younger individuals, and older patients are more likely to have progressive disease and high-risk prostate cancer at diagnosis. Given that PSA screening diagnoses mainly curable, early prostate cancer, screening decision could be offered to otherwise healthy elderly patients who are likely to benefit from aggressive treatment. Conclusion: Prostate-specific antigen screening is not officially recommended and most scientific associations promote shared decision making. While PSA screening decision is currently based on physician’s judgment, it is clear that a strict age cut-off of 75 years reduces over-screening, but also prohibits screening in healthy older men with a long life expectancy.